Generation of Magnon Orbital Angular Momentum by a Skyrmion-Textured Domain Wall in a Ferromagnetic Nanotube - Lee, Seungho; Kim, Se Kwon (Frontiers in Physics, 2022)
We develop a theory for the dynamics of a magnon on top of a domain wall in a ferromagnetic nanotube. Due to the geometry of the sample, domain walls are classified by the Skyrmion charge which counts the winding number of magnetic textures. The domain wall with a non-zero Skyrmion charge generates an emergent magnetic field for magnons, which exerts the Lorentz force on moving magnons and thereby deflects their trajectories. This deflection is manifested as the generation of the finite orbital angular momentum of the magnon that traverses the domain wall. We obtain exact solutions for the magnon on top of the Skyrmion-textured domain wall and also their scattering properties with the domain wall with the aid of supersymmetric quantum mechanics. We show that there is a critical wavenumber for the total reflection of magnons and it is discretized by the Skyrmion charge of the domain wall. Our results show that the orbital angular momenta of magnetic textures and magnons can be intertwined in a curved geometry.